Model of Leadership, Customer Loyalty, Work Discipline to Company Performance as Empirical Study on Profit Organization: A literature Riview - Aviyanti, Cut; Tubagus Hedi Saepudin; Rita Mulyanti (Dinasti International Journal of Digital Business Management, 2023)
The purpose of this paper is to determine the relationship between variables in the context of organizations with qualitative methods. This paper uses qualitative research methods by looking for paper literature related to the results or findings related to the variables in this paper, the findings obtained from the paper are proven in the profit organization in the implementation of the existing. Overall between variables where leadership with company performance or organizational performance exists in the findings of the paper from various literature found to support this paper and with the object of profit and non-profit organizations such as government organizations, insurance, schools, and others. The Work Discipline variable in the findings also has a positive influence on company performance or organizational performance, and finally customer loyalty in profit organizations as the object of research from existing literature also has a positive influence on company performance or organizational performance. So that this paper with a review of previous literature papers is proven even with minimal results.